Evaluation of antioxidant and anti-inflammatory activity of green coffee beans methanolic extract in rat skin. Issue 11 (2nd June 2020) - Pergolizzi, Simona; D'Angelo, Valeria; Aragona, Marialuisa; Dugo, Paola; Cacciola, Francesco; Capillo, Gioele; Dugo, Giacomo; Lauriano, Eugenia Rita
Abstract: Since a long time caffeine has been used in pharmaceutical and cosmetic preparations due to its favorable effects on the skin. The aim of this study was to evaluate the topical anti-inflammatory activity (carrageenan-induced paw oedema) of an ointment prepared using a methanolic extract from green beans of C. robusta via histology. Results showed that the treatment with the ointment reduced the paw oedema within 3 and 5 h post-carrageenan administration. The immunohistochemical evaluations of αSMA, Langerin and S100 gave further support to the morphological analysis. Finally, the methanolic extract from green beans of C. robusta proved to possess elevated free radical scavenger capability by DPPH assay, which may contribute to the observed anti-inflammatory activity. Graphical Abstract: